Pengaruh Pemberian Teknik Relaksasi Benson Terhadap Intensitas Nyeri Pasien Post Sectio Caesarea di RS Nuraida Bogor - Peti Fatma Meilani; Amalia Indah Puspitasari (Malahayati Nursing Journal, 2024)
ABSTRACT The World Health Organization reported in 2021, that the ratio of deliveries performed through Sectio Caesarea globally was 21% with the highest ratio being in East Asia (63%), Latin America and the Caribbean (54%), West Asia (50%), North Africa (48%), Southern Europe (47%) and Australia (45%). In Indonesia, 17.6% of women undergoing section caesarean delivery are associated with moderate to severe postoperative pain, which delays recovery and return to activities of daily living, damages mother-child bonding, impacts maternal psychological wellbeing and can complicate breastfeeding.Research Objective: To determine the effect of giving Benson relaxation technique on the pain intensity of post sectio caesarea patients. This study is a quantitative study using a quasi-experimental design and a one group pre-post test design approach. The population is post section Caesarea patients who are still in treatment as many as 35 people. The sampling technique used total sampling. The results showed that the majority of laboring women before being given benson relaxation experienced moderate post sc pain as many as 32 respondents (91%). After benson relaxation 30 respondents (100%) experienced a decrease in pain intensity to mild. The Wilcoxone range list test obtained a p-value of 0.000 0.005, which means that there is an effect of giving Benson Relaxation Techniques on the Pain Intensity of Post Sectio Caesarea Patients at Rs Nuraida Bogor. The results of the wilcoxone range list test obtained a p-value of 0.000 0.005 which Conclusion: The results of the wilcoxone range list test results obtained a p-value of 0.000 0.005, which means that there is an effect of giving Benson Relaxation Techniques on the Pain Intensity of Post Sectio Caesarea Patients at Rs Nuraida Bogor. It is hoped that this research can be read as a source of knowledge for the community and as a reference for the community in applying the Benson relaxation technique as an effort to relieve post sectio caesarea pain in oneself, family, and to the community. Keywords: Caessarea, Post Sectio Caesarea Pain, Benson Relaxation  ABSTRAK World Health Organization melaporakan pada tahun 2021, bahwa rasio persalinan yang dilakukan melalui Sectio Caesarea secara global adalah sebesar 21% dengan rasio tertinggi berada di Asia Timur (63%), Latin Amerika dan Karibean (54%), Asia Barat (50%), Afrika Utara (48%), Eropa Selatan (47%) dan Australia (45%). Di Indonesia 17,6% rasio perempuan menjalani persalinan secara section caesarea dikaitkan dengan nyeri sedang hingga berat pasca operasi sehingga menunda pemulihan dan kembalinya ke aktivitas kehidupan sehari-hari,merusak ikatan ibu dan anak, berdampak kepada kesejahteraan psikologis ibu dan dapat mempersulit pemberian ASI. Untuk mengetahui Pengaruh pemberian teknik relaksasi Benson terhadap intensitas nyeri pasien post sectio caesarea. Penelitian ini merupakan penelitian kuantitatif dengan menggunakan desain quasi eksperimen dan pendekatan one group pre-post test design. Populasi adalah pasien post section Caesarea yang masih dalam perawatan sebanyak 35 orang. Teknik pengambilan sampel menggunakan total sampling. Didapatkan hasil mayoritas ibu bersalin sebelum diberikan relaksasi benson mengalami nyeri post sc sedang sebanyak 32 responden (91%). Setelah dilakukan relaksasi benson 30 responden (100%) mengalami penurunan intensitas nyeri menjadi ringan. Uji wilcoxone range list didapatkan nilai p-value 0,0000,005 yang artinya terdapat Pengaruh Pemberian Teknik Relaksasi Benson Terhadap Intensitas Nyeri Pasien Post Sectio Caesarea Di Rs Nuraida Bogor. Hasil uji wilcoxone range list didapatkan nilai p-value 0,0000,005 yang artinya terdapat Pengaruh Pemberian Teknik Relaksasi Benson Terhadap Intensitas Nyeri Pasien Post Sectio Caesarea Di Rs Nuraida Bogor. Diharapkan penelitian ini dapat menjadi bahan bacaan sebagai sumber pengetahuan bagi masyarakat serta sebagai acuan masyarakat dalam menerapkan teknik relaksasi Benson sebagai upaya meredakan nyeri post sectio caesarea pada diri sendiri, keluarga, maupun kerabat. Kata Kunci: Caessarea, Nyeri Post Sectio Caesarea, Relaksasi Benson